Svenskehandelen som tok slutt - Torbjørn Kalberg (Scandinavian University Press/Universitetsforlaget, 2017)
Abstract Historical research on social development in the Scandinavian north used to be dominated by stories of ruthless taxation and economic exploitation of the Sami people. Stories of the violent actions of the so-called bircarlians were told again and again. These bircarlians were considered to be a group of greedy merchants originating from areas bordering on the Gulf of Bothnia. The old stories of evil tax collectors harassing the Sami are no longer universally accepted. Nowadays the bircarlians are described as locals, agriculturalists and traders engaged for centuries in exchanging goods with the Sami, benefiting both themselves and the indigenous nomads. The bircarlians used to be regarded as holders of royal privileges granting them special rights in the trade with the Sami. This view has also been challenged. The system involving Sami and local tradesmen seems to be much older than the impression given by Swedish authorities in the late middle ages. Bircarlian activities long outdated the royal Swedish colonization of the north. Their independent and decentralised trading traditions are now instead considered important stages in the development of the Swedish unitary national state.